Paricalcitol Pretreatment Attenuates Renal Ischemia-Reperfusion Injury via Prostaglandin E2 Receptor EP4 Pathway. (29th March 2017) - Hong, Yu Ah; Yang, Keum Jin; Jung, So Young; Park, Ki Cheol; Choi, Hyunsu; Oh, Jeong Min; Lee, Sang Ju; Chang, Yoon Kyung; Park, Cheol Whee; Yang, Chul Woo; Kim, Suk Young; Hwang, Hyeon Seok
Abstract : The protective mechanism of paricalcitol remains unclear in renal ischemia-reperfusion (IR) injury. We investigated the renoprotective effects of paricalcitol in IR injury through the prostaglandin E2 (PGE2 ) receptor EP4. Paricalcitol was injected into IR-exposed HK-2 cells and mice subjected to bilateral kidney ischemia for 23 min and reperfusion for 24 hr. Paricalcitol prevented IR-induced cell death and EP4 antagonist cotreatment offset these protective effects. Paricalcitol increased phosphorylation of Akt and cyclic AMP responsive element binding protein (CREB) and suppressed nuclear factor- κ B (NF- κ B) in IR-exposed cells and cotreatment of EP4 antagonist or EP4 small interfering RNA blunted these signals. In vivo studies showed that paricalcitol improved renal dysfunction and tubular necrosis after IR injury and cotreatment with EP4 antagonist inhibited the protective effects of paricalcitol. Phosphorylation of Akt was increased and nuclear translocation of p65 NF- κ B was decreased in paricalcitol-treated mice with IR injury, which was reversed by EP4 blockade. Paricalcitol decreased oxidative stress and apoptosis in renal IR injury. Paricalcitol also attenuated the infiltration of inflammatory cells and production of proinflammatory cytokines after IR injury. EP4 antagonist abolished these antioxidant, anti-inflammatory, and antiapoptotic effects. The EP4 plays a pivotal role in the protective effects of paricalcitol in renal IR injury.